Navigating aspirations and expectations: adolescents' considerations of outmigration from rural eastern Germany - Meyer, Frank (Journal of ethnic and migration studies, 2018)
From the perspective of policymakers, young people are often regarded as the most important group for the future development of rural regions experiencing socioeconomic polarisation. They, in turn, usually see themselves and their desire to migrate not as the driving force of population decline, but as a symptom of it. Although politicians urge adolescents to not leave rural regions despite the hard times, adolescents expressly do so because of the socioeconomic conditions and limited local opportunities. Drawing on a case study of Altenburger Land - a rural district in eastern Germany suffering from limited job opportunities for adolescents, outmigration and negative depictions in the media - this article aims to explain the conditions of migration and their impact on adolescent migratory decision-making. In sum, adolescents' choices happen in a nexus of social relations, emotions and political programmes. Besides their own attempts of becoming, these contested fields of expectations from different entities create a norm-driven array of discourses permeating many aspects of their lives. Therefore, migration in this context can be considered as a product of spatial and spatialised discourses through which a subject must navigate.